Biennial acorn maturation and its relationship with flowering phenology in Iberian populations of Quercus suber (Trees, 2004)
Since the XIX century, there is a controversy about the existence of biennial maturation of the acorns in Quercus suber L. While some authors recognised biennial cycles as an adaptation to habitats with short vegetative periods, other authors discarded the biennial pattern. Successive flowering events from spring to autumn and annual acorn ripening are proposed as an explanation of the multiple acorn crops typical of Iberian forests. To clarify this discussion, the presence of annual and biennial acorns was assessed in seven cork oak stands, covering a wide range of environmental conditions. In each stand, 100 individuals were sampled once in spring and once in autumn. Biennial acorns were observed with variable frequencies in all populations. There was a significant and positive relationship between latitude and the percentage of trees with biennial acorns within northern and central populations. On the contrary, this trend was not significant among southern populations. The hypothesis that the presence of biennial acorns in Quercus suber is related to individual female flowering phenology was confirmed in four populations located in the southwestern Iberian Peninsula. Unregarding local differences in the distribution of phenological stages anticipated trees bore significantly less biennial acorns than delayed individuals of the same stand. This result is coherent with the idea that the length of the vegetative period plays a crucial role in the frequency of annual and biennial acorn ripening patterns. The relationship between annual and biennial ripening cycles and the multiple acorn crops is discussed